PERFORMATIVE DIMENSION OF FAMILY SOCIAL CAPITAL IN MARITAL INTERACTIONS - Tayyaba Sohail; Ahmed Usman; Tayyaba Sohail; Ahmed Usman (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The family social capital is an embedded resource in family networks which can be utilized by spouses in defining and shaping their marital interaction. Family networks can neither be created nor operated in isolation and same is applicable to the marital interaction of spouses. The norms of the society guide the structural and relational dynamics of family networks. These dynamics provide a conducive environment for operating of family social capital within the family networks. The current study aims to explore the normative orientation of the family networks about spousal roles, in detail, to understand the functioning of family social capital in shaping marital interaction. Using the interpretive research paradigm, the chosen methodology of the study is qualitative. 20 married couples were recruited from Lahore using purposive sampling. The data was collected through in-depth interviews and a semi-structure interview guide was used as a tool to tap detailed experiences of the spouses. The results were derived through thematic analysis. The findings of the study showed that role of spouses is clearly categorized in two domains. Private domains, which are specific to housed-hold activities, are considered responsibility of women. Public Domains, related activities as bread earning, are the responsibility of the male spouse. The mothers-in-law were found to be active actor of family networks in conforming the marital performances of the spouses in accordance with normative orientation of family networks. The family social capital is playing a two pronged role. On one side it is acting as a helpful feature for the male to achieve his role expectations whereas the on the other hand, it is acting as a restraining factor against the female. In reinforcement of gender norms in marital interaction, family social capital is being decapitalized and causing conflict between spouses which is negatively affecting the quality of marital relations.